2015
DOI: 10.18632/oncotarget.5635
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-regulated delivery of lincRNA-p21 suppresses β-catenin signaling and tumorigenicity of colorectal cancer stem cells

Abstract: Cancer stem cells (CSCs) are key cellular targets for effective cancer therapy, due to their critical roles in cancer progression and chemo/radio-resistance. Emerging evidence demonstrates that long non-coding RNAs (lncRNAs) are important players in the biology of cancers. However, it remains unknown whether lncRNAs could be exploited to target CSCs. We report that large intergenic non-coding RNA p21 (lincRNA-p21) is a potent suppressor of stem-like traits of CSCs purified from both primary colorectal cancer (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 50 publications
3
62
0
Order By: Relevance
“…For instance, Wang et al . found that lincRNA-p21 suppresses β-catenin signaling and tumorigenicity of colorectal cancer stem cells [38]. In line with it, we found that lincRNA-p21 suppresses Wnt/β-catenin signal through sponging miR-17-5p.…”
Section: Discussionsupporting
confidence: 82%
“…For instance, Wang et al . found that lincRNA-p21 suppresses β-catenin signaling and tumorigenicity of colorectal cancer stem cells [38]. In line with it, we found that lincRNA-p21 suppresses Wnt/β-catenin signal through sponging miR-17-5p.…”
Section: Discussionsupporting
confidence: 82%
“…Long non‐coding RNAs (lncRNAs) constitute a novel heterogeneous class of non‐coding RNAs, which range from 200 nucleotides to multiple kilobases and account for much of the transcribed genome . Increasing evidence has demonstrated the key roles of lncRNAs in regulating multiple major physiological and pathological processes, including proliferation, cell growth, apoptosis, metastasis, metabolism, development, differentiation, senescence, self‐renewal, stem‐cell pluripotency, immune response, and drug resistance . Epithelial‐to‐mesenchymal transition (EMT) is one of the underlying mechanisms of colonic cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…8 Increasing evidence has demonstrated the key roles of lncRNAs in regulating multiple major physiological and pathological processes, including proliferation, cell growth, apoptosis, metastasis, metabolism, development, differentiation, senescence, self-renewal, stem-cell pluripotency, immune response, and drug resistance. [9][10][11][12][13][14][15] Epithelial-to-mesenchymal transition (EMT) is one of the underlying mechanisms of colonic cancer progression. LncRNA HOTAIR, H19, CCAT1, ATB, and BANCR, through a variety of mechanisms, can promote the EMT process, or its converse MET process, in colorectal cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence reports that multiple miRNAs are differently expressed and dysregulated in tumour tissues, or in colon cancer patients, compared with adjacent tissues or with healthy controls, respectively . Although previous studies have amply reported the role of miR‐21 (miR‐21‐5p) in the progress of CRC cells, which has been recognized as an oncogene associated with cancer initiation, progression, and metastasis, the role of the miR‐21 passenger strand (miR‐21‐3p) in the proliferation, apoptosis and invasion of CRC cells has not been fully clarified . This study aimed to investigate the role of miR‐21‐3p and its target gene in CRC cells.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs have been found to regulate many physiological development processes including cell proliferation, apoptosis and differentiation, and participate in various pathological processes including carcinogenesis and metastasis . MiRNA expression levels are found to be altered in especially most tumour types including CRC . Yang et al reported that miR‐21, which has been one of the best studied miRNAs, controls human telomerase reverse transcriptase via PTEN in human colorectal cancer cell proliferation.…”
Section: Introductionmentioning
confidence: 99%